Proposed skill builder series for Filipino high school students, grade level 7.0-7.4 Ruby set - Cabajon, Antonia Fortuito (1977)
This paper constituted a part of a series of multilevel developmental reading exercises patterned after the SRA Reading Laboratory and the Reader's Digest Skill Builders. These graded instructional materials aimed to develop the different comprehension skills, vocabulary and word analysis skills in high school students. Observations and results of government examinations and researches showed that students in the secondary schools lack the necessary reading skills that would serve as principal tools in coping with the varied curricular offerings of the modern schools.
"March 1977."
Thesis (M.A.T.Reading)--University of the Philippines, Diliman.
Keywords: Readers (Secondary); Reading (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices